Analisis Dampak Strategic Lawsuit Against Public Participation (SLAPP) Terhadap Perlindungan Lingkungan di Indonesia - Ricki Rahmad Aulia Nasution; Adnan Hasanudin; Muhammad Rausyan Fikry; Irwan Triadi (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Strategic Lawsuit Against Public Participation (SLAPP) has posed a serious challenge to environmental protection in Indonesia. Cases such as Walhi vs PT Jatim Jaya Perkasa and PT Bumi Mekar Hijau vs the Government of South Sumatra Province and Walhi illustrate how SLAPP is used by corporations to intimidate and silence environmental activists. This article analyzes the mechanisms and strategies of SLAPP as well as its psychological and social impacts. The literature study method is employed to gather data from various sources. The conclusion is that SLAPP not only has legal implications but also imposes heavy psychological and social burdens on activists, including fear, isolation, and social polarization within communities. Therefore, strong legal protection, increased civil society capacity, and cross-sectoral collaboration are needed to combat SLAPP practices and ensure a more conducive environment for sustainable and effective environmental advocacy.